Mechanical and Microstructural Characterization of Cement Mortars Prepared by Waste Foundry Sand (WFS) - Çevik, S.; Mutuk, T.; Mesci, B.M.; Demirbaş, A.K. (Springer International Publishing b.ben-nissan@uts.edu.au, 2017)
Foundry sand is used spent in sand molds of ferrous and non-ferrous industries. When it is no longer used, it has become solid wastes generated by foundries. According to European Union regulations, it is a non-hazardous waste so it can be recycled in other industries, especially in cement industry. In the present paper, the mechanical properties and characterization of cement mortars are prepared by using waste foundry sand coming from Turkey steel manufacturer as partial replacement of natural sand were experimentally investigated and the possibility of using waste foundry sand (WFS) instead of natural sand in mortar has been determined. Recycling of solid foundry waste is considered as an environmentally friendly alternative to solve the problem of disposing of the solid wastes. Cement mortar admixtures were prepared by using with variable percentages of WFS ranging from 15 to 60%. Additionally, to make comparison, one reference admixture sample was fabricated without using any waste foundry sand. The effect of WFS on the compressive strength of the cement mortar was analyzed. The compressive strengths values of all the specimens were recorded for 3, 7, and 28 days and results showed that when the amount of WFS replacement is increased, the strength decreased slightly according to the comparison of the reference sample. However, cement mortar containing 15% additive has showed the highest strength value at 3 and 28 days. As a result in the present study, it is observed that optimum additive amount of WFS as replacement of natural sand in cement mortar is 15%. SEM images were also taken to evaluate the relationship between microstructure and strength of the specimens. Moreover, scanning electron microscope (SEM) examination was carried out to explain the effectiveness of the matrix in the reuse of WFS. Microstructural observation of the samples by SEM showed that the sand particles of the WFS were well embedded in the cementitious matrix. © 2017 Australian Ceramic Society.
Keywords: Cement Mortar; Mechanical Treatment; Microstructure; Waste Foundry Sand